Evidence summary on the rehabilitative management of dysphagia during radiotherapy for head and neck cancer patients - Zhang, Yu; Wan, Hongwei; Zhu, Yu; Wang, Shuman; Zheng, Mimi; Li, Xiaoru (Frontiers in Oncology, 2024)
ObjectiveTo retrieve, extract, integrate and evaluate evidence on the rehabilitation of dysphagia in patients undergoing radiotherapy for head and neck cancer (HNC), and to provide a basis for the development of a rehabilitation management protocol for dysphagia in patients undergoing radiotherapy for HNC.MethodsAn evidence-based systematic search of the literature related to the rehabilitation of dysphagia in patients with HNC during radiotherapy was conducted from January 2013 to March 2023, and the corresponding evaluation tools were selected according to the different types of literature for quality evaluation. “The Joanna Briggs Institute (JBI) evidence pre-grading system was used to evaluate the quality of the evidence.ResultsA total of 17 articles were included, including 3 guidelines, 5 expert articles, 1 clinical decision, 1 practice recommendation, 2 evidence summaries and 5 systematic evaluations. A final total of 28 pieces of evidence were summarised, including 6 areas of swallowing disorder screening and assessment, physiotherapy, preventive swallowing function training, feeding management, pain control, and oral care.ConclusionThis study forms a multidisciplinary collaborative evidence summary for the rehabilitation management of dysphagia in patients undergoing radiotherapy for HNC, but the application of some of the evidence needs to be carried out in the context of the clinical setting and patient-specific circumstances for the rehabilitation evidence selected for patients’ dysphagia to improve their swallowing function and their swallowing-related quality of life and reduce the occurrence of related complications.